Changer de point de vue ! De la difficulté malheureuse à l'épreuve constructive : un effet des recherches collaboratives ? - Pablo Buznic-Bourgeacq; Anne-Laure Le Guern; Jean-François Thémines (Éducation et Socialisation)
This paper provides an original conceptualization of test, based on social, clinical and didactics dimensions. The purpose is to analyse many difficulties encoutered by teachers, reflections of both social context and subjective experience. This conceptualization is illustrated by feedback on collaborative research, which supported or reinforced those. At last, this paper points out the conditions under wich researchers can ercercise their responsabilty towards those who are involved in these researches until they can be considered as co-authors, meanwhile they analyse the situation et recover their profession. This is thus the meaning of constructive value of test.